Shrinking and growing metropolitan areas - asymmetric real estate price reactions? The Case of German single-family houses - Lisa Dust; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
The population of Germany will be one of the first in the western hemisphere to undergo considerable permanent shrinkage. In view of the relatively low elasticities of supply and demand significant negative price reactions might be expected. This work supplements existing studies by estimating real estate prices for single-family homes on the disaggregate level of Germany's metropolitan areas. It highlights asymmetric price reactions: growth in population numbers has no significant price effects, whereas declining population numbers lead to significant negative price effects.
Keywords: R12; R21; R31; 330; shrinking population; real estates; asymmetric price reactions; regional analysis